Attracting Stakeholders to the Implementation of the Program for the Region's Socio-Economic Security (Economics and region, 2019)
The article defines the essence of the concept of “stakeholders in the program of strengthening the socio-economic security of the region”. The benefits and risks of attracting stakeholders to meet the objectives of the program to strengthen the regional socio-economic security are identified. It is justified that the implementation of these risks has a negative impact on the program objectives fulfillment to strengthen the regional socio-economic security. Consequences of implementing the risks of attracting stakeholders to solve problems under the program to strengthen the regional socio-economic security are explained. The principal ways to overcome the risks of attracting stakeholders to solve the problems of the program for strengthening the regional socio-economic security are suggested.
Keywords: stakeholders; region; security; program; socio-economic security of the region; benefits; risks; regional development program